Determination of repeatability and reproducibility of EBC accepted methods: V – Beer: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Benard, M. (BrewingScience, 2000)
Methods published in Analytica-EBC for the determination of Beer Alcohol (9.2.1), Real, Apparent and Original Extracts(9.4), Real Degree of Fermentation (9.5), Colour (9.6), Final Attenuation (9.7), Bitterness (9.8), Total Nitrogen (9.9.1), FreeAmino Nitrogen (9.10), Total Polyphenols (9.11), Vicinal Diketones (9.24.1), Total Carbohydrate (9.26) and FermentableCarbohydrate (9.27) have been collaboratively tested by the European Brewery Convention Analysis Committee accordingto the ISO standard 5725. Repeatability (r₉₅) and reproducibility (R₉₅) values are presented.